Teachers' expectations of children with Down Syndrome starting school in the United Arab Emirates or United Kingdom. Issue 4 (8th August 2019) - Takriti, Rachel A.; Atkinson, Susan J.; Elhoweris, Hala
ABSTRACT: Starting school has been shown to correlate with later school outcomes. Teachers working in early years' settings either in the United Arab Emirates (UAE) or the United Kingdom completed a questionnaire asking them to rate the importance of 20 statements in answer to the question 'How important are the following for deciding whether a child with Down Syndrome has had a successful first two terms of school?' Findings demonstrated a different pattern of expectations depending on where the teacher was working. Specifically, teachers in the United Kingdom placed more importance on academic performance and the relationship with the family. Some similarities in the rankings of the scales were also obtained. Teachers, regardless of the location, placed most importance on children's happiness and knowledge of school routines in successfully starting school. Implications for children with Down Syndrome starting school in the UAE and the United Kingdom are discussed.